Bentuk Kesejahteraan Sosial Berbasis Gender Dalam Sistem â€œTandurâ€ Pada Pertanian Sawah Di Desa Sei Buluh Estate Kabupaten Serdang Bedagai - Desy Desvira (Universitas Muhammadiyah Sumatera Utara, 2023)
This study focuses on forms of gender-based social welfare in the tandur system in Sei Buluh Estate Village, Serdang Bedagai Regency. The purpose of this study is to understand the forms of gender welfare in tandur farmers, especially for women. This study uses a qualitative descriptive method. Data collection techniques used are primary and secondary techniques such as observation and interviews as well as collecting data related to research sourced from journals. The results of this study indicate that there are forms of gender inequality in the tandur system at the research location, such as exploitation of employees, gender double burden, economic welfare that has not increased in the last two years, and gender inequality in the portion of work. Based on the results of the research that has been done, it can be concluded that many women experience injustice in terms of work. The advice that can be given is to keep working so that you can get maximum results.